1996
DOI: 10.1002/adma.19960081214
|View full text |Cite
|
Sign up to set email alerts
|

Optical and structural properties of new discotic acrylates polymerized in the discotic nematic phase

Abstract: Discotic liquid crystals can be used as optical compensation layers to improve the viewing angle of twisted nematic liquid crystal displays, for example. The in situ photopolymerization of newly synthesized acrylates is shown to result in oriented films with a negative birefringence. The transition temperatures, birefringence, and thermal stability were measured and the structure of the polymers was determined by wide‐angle X‐ray diffraction in order to explain the difference in optical properteis between vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 17 publications
1
17
0
2
Order By: Relevance
“…Because of the frozen nature of mer [8]. In the present case, a pretransitional arrangement cannot justify the relatively high birefringence of poly (1), the extrapolation method of Haller cannot be applied.…”
Section: Biref Ringence Of Oriented Thin ® Lms Prepared From Compoundmentioning
confidence: 82%
See 2 more Smart Citations
“…Because of the frozen nature of mer [8]. In the present case, a pretransitional arrangement cannot justify the relatively high birefringence of poly (1), the extrapolation method of Haller cannot be applied.…”
Section: Biref Ringence Of Oriented Thin ® Lms Prepared From Compoundmentioning
confidence: 82%
“…organic layer was dried over MgSO 4 and evaporated. The intermediate product 8 and pyridinium p-tolueneThe organic layer was dried over anhydrous magnesium sulphate and the solvent was evaporated. The resulting sulphonate (3.11 g, 0.012 mol) were dissolved in 80 ml of ethanol and heated to 60ß C (to remove the THP solid product was shaken 3 times with 20 ml of ethanol to remove the unreacted side group materials.…”
Section: Syntheses Of the Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been observed that small methyl substituents at the para position on the benzoate moieties depress mesophase transition temperatures, broaden liquid crystal windows and influence phase sequences of these compounds [13,14]. Based on acrylated benzoate esters of 2,3,6,7,10,11-hexahydroxytriphenylene, stable anisotropic films have been obtained by photopolymerisation [15,16]. It is also known that introduction of large bulky substituents causes thickening of the molecules and weakens the face-to-face interactions.…”
Section: Introductionmentioning
confidence: 98%
“…Particularly, polymerizable liquid crystalline (PLC) materials have been widely used for producing brightness enhancement films [1], reflective polarizers [2,3], compensation films [4][5][6], and retarders [7][8][9] in liquid crystal 25 displays (LCDs). In these cases, the PLC should be processed into an optically anisotropic film structure where an alignment layer is typically needed for orienting the PLC molecules.…”
Section: Introductionmentioning
confidence: 99%